Levansucrase from Halomonas smyrnensis AAD6(T): first halophilic GH-J clan enzyme recombinantly expressed, purified, and characterized - TOKSOY ÖNER, EBRU (SPRINGER, 2018)
Fructans, homopolymers of fructose produced by fructosyltransferases (FTs), are emerging as intriguing components in halophiles since they are thought to be associated with osmotic stress tolerance and overall fitness of microorganisms and plants under high-salinity conditions. Here, we report on the full characterization of the first halophilic FT, a levansucrase from Halomonas smyrnensis AAD6(T) (HsLsc; EC 2.4.1.10). The encoding gene (lsc) was cloned into a vector with a 6xHis Tag at its C-terminus, then expressed in Escherichia coli. The purified recombinant enzyme (47.3kDa) produces levan and a wide variety of fructooligosaccharides from sucrose, but only in the presence of high salt concentrations (>1.5M NaCl). HsLsc showed Hill kinetics and pH and temperature optima of 5.9 and 37 degrees C, respectively. Interestingly, HsLsc was still very active at salt concentrations close to saturation (4.5M NaCl) and was selectively inhibited by divalent cations. The enzyme showed high potential in producing novel saccharides derived from raffinose as both fructosyl donor and acceptor and cellobiose, lactose, galactose, and -arabinose as fructosyl acceptors. With its unique biochemical characteristics, HsLsc is an important enzyme for future research and potential industrial applications in a world faced with drought and diminishing freshwater supplies.
Keywords: Levansucrase; Fructosyltransferase; Halophilic enzyme; Halomonas smyrnensis; Levan; Fructan; BACILLUS-SUBTILIS LEVANSUCRASE; ZYMOMONAS-MOBILIS; FRUCTOSYLTRANSFERASE LEVANSUCRASE; FRUCTO-OLIGOSACCHARIDES; INULOSUCRASE ENZYMES; ERWINIA-AMYLOVORA; CRYSTAL-STRUCTURE; LEVAN; SUCROSE; BIOSYNTHESIS